2017
DOI: 10.1016/j.apcatb.2017.06.070
|View full text |Cite
|
Sign up to set email alerts
|

VOC ternary mixture effect on ppb level photocatalytic oxidation: Removal kinetic, reaction intermediates and mineralization

Abstract: This work addresses photocatalytic oxidation for indoor air purification and more especially the key and realistic issue of VOC mixture treatment. The VOC mixture effect needs to be investigated since indoor air contains several tens of VOCs which may impact photocatalytic oxidation performances. In order to be closer to realistic conditions, concentrations in the ppb range were used and toluene, decane and trichloroethylene (TCE) were treated first as single compounds, then as an equimolar ternary mixture und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 35 publications
5
42
0
Order By: Relevance
“…In this experiment, competition adsorption of pollutants on the photocatalysts active sites. This behavior is similar to what it was reported by Debono et al [37]. The latter evidenced the inhibitive effect along the photocatalytic degradation of three VOCs mixture.…”
Section: Effect Of Initial Concentration Increase On Photocatalytic Osupporting
confidence: 91%
“…In this experiment, competition adsorption of pollutants on the photocatalysts active sites. This behavior is similar to what it was reported by Debono et al [37]. The latter evidenced the inhibitive effect along the photocatalytic degradation of three VOCs mixture.…”
Section: Effect Of Initial Concentration Increase On Photocatalytic Osupporting
confidence: 91%
“…This can be attributed to the reactive species generated in the reaction medium. This will not be further discussed in the present study and more details can be found in the literature and in our previous publications [33][34][35][36]. Figure 7 shows the RE for a pure and mixed system in the presence of the photocatalyst and the light source.…”
Section: Effect Of the Injected Voltage During Ntp Processmentioning
confidence: 99%
“…The degradation dynamics of the two pollutants separately seems to happen faster than when they are mixed. It is likely that this is linked to the competition of pollutants on the active sites of photocatalyst [34]. combined process, the RE reaches a value higher than 60% for a voltage equal to 9 kV.…”
Section: Effect Of the Injected Voltage During Ntp Processmentioning
confidence: 99%
“…To study the promptness of conversion of a compound and its reaction intermediates to CO 2 , Debono et al [70] suggested that the mineralization rates be plotted as a function of the conversion rates. The results are acrylonitrile conversion rate vs mineralization rates for the three concentrations studied are shown in Fig.…”
Section: Mineralization Rates Obtained During the Degradation Of Acrymentioning
confidence: 99%